Dual threat: Rhizopus and Staphylococcus hemolyticus in acute mediastinitis in an immunocompetent host - Cheong, Xiong Khee; Zainulabid, Ummu Afeera; Kori, Najma; Chang, W.X.; Chuan Hun, Ding; Khaithir, Tzar Mohd Nizam; Periyasamy, Petrick (Elsevier Ltd, 2025)
Mediastinitis or sternal wound infection is a serious complication following coronary bypass surgery. The commonest causative organisms are Staphylococci and gram-negative bacteria. Fungal sternal wound infection, in particular molds, is rarely reported. It is usually associated with high morbidity and mortality. We described a case of a male with concurrent mucormycosis and staphylococcal sternal wound infection post bypass heart surgery, treated successfully with isavuconazole.